Mathematical submodels in water quality systems - Jrgensen, Sven Erik, 1934-; Gromiec, Marek Jerzy (Developments in environmental modelling, 1989)
The use of models to assess water quality is becoming increasingly important worldwide. In order to be able to develop a good model, it is necessary to have a good quantitative and ecological description of physical, chemical and biological processes in ecosystems. Such descriptions may be called ``submodels''. This book presents the most important, but not all, submodels applied in water quality modelling. Each chapter deals with a specific physical process and covers its importance, the most applicable submodels (and how to select one), parameter values and their determination, and futur.